Providing a Model for Marital Burnout based on attachment styles in married people: Differentiation with mediating role - Asadi, Mehran; Pourebrahim, Taghi; Farrokhi, Noorali; Davaee, Mahdi (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The aim of this study was to develop a model of marital boredom based on attachment styles in married people: with a mediating role of differentiation. Methods: In terms of the applied purpose of the research, the research design was descriptive and the type of correlation was modeling. The statistical population of the present study included all young married men and women between the ages of 20-35 who referred to psychology and counseling clinics in Tehran using the sampling method available to 480 people (289 females, 191 males) as a sample were chosen. Data were collected using the Pinner Marital Boredom Scale (1996), the Scorne and Friedlander (1998) Differentiation Questionnaire, and the Collins and Reed Adult Attachment Style Questionnaire (1990). Results: The results showed that there was a significant negative relationship between marital differentiation and boredom, Also, differentiation has a negative relationship with insecure attachment styles (ambiguous / avoidant) and on the other hand has a positive and significant relationship with insecure attachment style and has a mediating role in the relationship between avoidant attachment style and marital boredom (P